Simulated airway drills as a tool to measure and guide improvements in endotracheal intubation preparation in the paediatric emergency department. (4th June 2021) - Wong, Kei U; Gross, Isabel; Emerson, Beth L; Goldman, Michael P
Abstract : Introduction: Emergent paediatric intubation is an infrequent but high-stakes procedure in the paediatric emergency department (PED). Successful intubations depend on efficient and accurate preparation. The aim of this study was to use airway drills (brief in-situ simulations) to identify gaps in our paediatric endotracheal intubation preparation process, to improve on our process and to demonstrate sustainability of these improvements over time in a new staff cohort. Method: This was a single-centre, simulation-based improvement study. Baseline simulated airway drills were used to identify barriers in our airway preparation process. Drills were scored for time and accuracy on an iteratively developed 16-item rubric. Interventions were identified and their impact was measured using simulated airway drills. Statistical analysis was performed using unpaired t-tests between the three data collection periods. Results: Twenty-five simulated airway drills identified gaps in our airway preparation process and served as our baseline performance. The main problem identified was that staff members had difficulty locating essential airway equipment. Therefore, we optimised and implemented a weight-based airway cart. We demonstrated significant improvement and sustainability in the accuracy of obtaining essential airway equipment from baseline to postintervention (62% vs 74%; p=0.014), and postintervention to sustainability periods (74% vs 77%; p=0.573). Similarly, we decreased and sustained the time (in seconds) required to prepare for a paediatric intubation from baseline to postintervention (173 vs 109; p=0.001) and postintervention to sustainability (109 vs 103; p=0.576). Conclusions: Simulated airway drills can be used as a tool to identify process gaps, measure and improve paediatric intubation readiness.